Respon Muslim Bali terhadap Pergub 79 Tahun 2018 tentang Aturan Penggunaan Busana Adat Bali - Sudarsono, Sudarsono (Proceedings of Annual Conference for Muslim Scholars, 2019)
Culture is something that is vulnerable to change according to the times. So as to preserve and preserve the culture that is in the midst of society, it takes efforts and solutions to maintain the culture that has long been preserved. Thus, when an area in our country becomes a tourist destination of various regions of the archipelago and abroad, it becomes natural that there are fears of a change in culture and then an initiative to properly guard it will emerge. Therefore, the Governor of Bali issued a regulation on the use of traditional Balinese clothes, because he was worried that Balinese culture would be eroded by foreign cultures who came to Bali. This is very clear from the purpose of making the Governor of Bali related to the use of traditional Balinese clothing, namely maintaining and maintaining the preservation of Balinese Traditional Clothing in order to strengthen identity, character, and character.